Tanggung Jawab Direksi Perseroan Terbatas Atas Tindakan Ultra Vires - Hasbullah F. Sjawie (Faculty of Law, Trisakti University, 2017)
An act which taken by directors of perseroan terbatas (Indonesia company limited by share) beyond the power of the perseron terbatas or outside its object clause as defined in its memorandum of article is referred as ultra vires. While perseroan terbatas is a legal entity, the law places the perseroan terbatas as a legal subject beside the human being. One of the differect between the two legal subjects is that perseroan terbatas can act in legal traffic only and limited to its object clause. As a universal dotrine in the company law, like stated in the Law No. 40 Year 2008 too, ultra vires doctrine will cause the director as a person to responsible of all acts beyond the perseroan terbatas power which his has taken under and on behalf of the perseroan terbatas. Key words: Company, director, ultra vires